2005
DOI: 10.1021/ja042192u
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Applications of Plasmon-Induced Charge Separation at TiO2 Films Loaded with Gold Nanoparticles

Abstract: Plasmon-induced photoelectrochemistry in the visible region was studied at gold nanoparticle-nanoporous TiO(2) composites (Au-TiO(2)) prepared by photocatalytic deposition of gold in a porous TiO(2) film. Photoaction spectra for both the open-circuit potential and short-circuit current were in good agreement with the absorption spectrum of the gold nanoparticles in the TiO(2) film. The gold nanoparticles are photoexcited due to plasmon resonance, and charge separation is accomplished by the transfer of photoex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
1,666
4
10

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,899 publications
(1,715 citation statements)
references
References 33 publications
35
1,666
4
10
Order By: Relevance
“…The excitation of plasmon resonances has been used to perform photocatalysis and charge transfer. 8,9 The "plasmon resonance" is however lossy, and the absorbed energy is quickly converted into heat. In addition, if the particles are supported by a solid, heat transfer from the particles does not necessary obey classical heat conduction.…”
mentioning
confidence: 99%
“…The excitation of plasmon resonances has been used to perform photocatalysis and charge transfer. 8,9 The "plasmon resonance" is however lossy, and the absorbed energy is quickly converted into heat. In addition, if the particles are supported by a solid, heat transfer from the particles does not necessary obey classical heat conduction.…”
mentioning
confidence: 99%
“…First, Tatsuma et al [37,38,45] and other workers [42,46] proposed that the photoexcited electrons in the metal nanoparticles transferred from the metal particle to the TiO2 conduction band since the photoresponse of these metal-TiO2 diode structures was consistent with the absorption spectra of Au or Ag nanoparticles. Second, Kamat et al [43,44] and Li et al [47] have suggested that the noble metal nanoparticles act as electron sinks or traps in the metal-TiO2 diode structures to accumulate the photogenerated electrons, which could minimize charge recombination in the semiconductor films.…”
Section: Review Of Metal-insulator-metal (Mim) Diodesmentioning
confidence: 94%
“…However, in these recent metal-TiO2 Schottky diode structures [37][38][39][40][41][42][43][44][45][46][47], it would appear that the barrier layer was actually quite a bit thicker than 10 nm (probably in excess of 1 um) and further details was unable to be found in these papers. Semi-classical models did not account for non-equilibrium energy distributions of carriers, or do so through a localize lattice temperature.…”
Section: Theoretical Modeling Of Ag-tio2-ti Mim Diodesmentioning
confidence: 98%
See 2 more Smart Citations